Effects of Military Service on Earnings and Education Revisited Variation by Service Duration, Occupation, and Civilian Unemployment - Martorell, Paco (RAND Corporation, 2014)
This report examines how military service affects earnings, especially how these effects differ by the number of years of service and military occupational specialties and how external factors and policies affect these impacts. The authors also examined how economic conditions in the civilian labor market when individuals exit active duty affect postservice earnings.